2021
DOI: 10.4014/jmb.2107.07022
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Visual Detection of Vibrio parahaemolyticus in Aquatic Foods Using blaCARB-17 Gene-Based Loop-Mediated Isothermal Amplification with Lateral Flow Dipstick (LAMP-LFD)

Abstract: Vibrio parahaemolyticus is recognized as one of the most important foodborne pathogens responsible for gastroenteritis in humans. The bla CARB-17 gene is an intrinsic β-lactamase gene and a novel species-specific genetic marker of V. parahaemolyticus. In this study, a loop-mediated isothermal amplification (LAMP) assay combined with a lateral flow dipstick (LFD) was developed targeting this bla CARB-17 gene. The specificity of LAMP-LFD was ascertained by detecting V. parahaemolyticus ATCC 17802 and seven other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Data from previous published studies have demonstrated that the TLH gene is conserved in all V. parahaemolyticus strains and has been suggested as a good target for the detection of all V. parahaemolyticus strains [38][39][40]. For the identification of pathogenic V. parahaemolyticus strains, toxR [38], 16-23s rRNA [38], or bla CARB-17 [41] have been previously used. However, the TDH gene is commonly reported among pathogenic strains and has been recommended as a robust target for the identification of pathogenic V. parahaemolyticus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Data from previous published studies have demonstrated that the TLH gene is conserved in all V. parahaemolyticus strains and has been suggested as a good target for the detection of all V. parahaemolyticus strains [38][39][40]. For the identification of pathogenic V. parahaemolyticus strains, toxR [38], 16-23s rRNA [38], or bla CARB-17 [41] have been previously used. However, the TDH gene is commonly reported among pathogenic strains and has been recommended as a robust target for the identification of pathogenic V. parahaemolyticus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Non-hybridized FITC probes attach to gold-labelled anti-FITC antibodies, generating a biotin-free double complex that travels from the test to the control line. The detection sensitivity with extracted genomic DNA was 600 fg/reaction for Mycoplasma pneumoniae [ 82 ], 100 fg/reaction for methicillin-resistant Staphylococcus aureus (MRSA) [ 83 ], and Pseudomonas aeruginosa [ 84 ] 630 fg/reaction for V. parahaemolyticus [ 85 ] and 13.5 fg/µL for Salmonella [ 86 ]. For obtaining a higher sensitivity and accuracy, nanomaterials and enzymatic enhancements were investigated by various research groups.…”
Section: Lamp Detection Methodsmentioning
confidence: 99%
“…However, PCR methods typically require specialized and expensive equipment, complex testing procedures, and skilled operators, making rapid testing inconvenient in nonspecialized laboratories or non-laboratory settings [12] . Isothermal amplification techniques, such as recombinase polymerase amplification (RPA) and loop-mediated isothermal amplification (LAMP), are increasingly being used for the rapid nucleic acid detection of pathogens in non-laboratory settings because they do not require specialized equipment or skilled personnel [13] , [14] , [15] . These isothermal amplification techniques have their own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%